2020
DOI: 10.3390/antibiotics9070364
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-Tuberculosis Activity of the Extracts and Their Active Components of Anogeissus leiocarpa (DC.) Guill. and Perr. with Special Emphasis on Polyphenols

Abstract: In Sudanese traditional medicine, decoctions of the stem bark of Anogeissus leiocarpa are used for the treatment of tuberculosis (TB). However, this plant has not been investigated before for its antimycobacterial effects. Our screening results show, for the first time, that many extracts of various parts of A. leiocarpa exhibit growth inhibitory activity against Mycobacterium smegmatis. Minimum inhibitory concentration (MIC) values ranged between 625 and 5000 µg/mL, with an ethyl acetate extract of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
(84 reference statements)
1
7
0
1
Order By: Relevance
“…On the other hand, and in consonance with Orlando et al [ 43 ], we observed that the polyphenol extraction yields were considerably varied between different plant parts. In a recent study, and in agreement with our results, Salih et al [ 44 ] did not obtain a good polyphenol extraction from macerated or decocted samples when using water as an extractant, in comparison with methanol and ethanol. These results were attributed to the lower polyphenol extraction yield obtained when water was used.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, and in consonance with Orlando et al [ 43 ], we observed that the polyphenol extraction yields were considerably varied between different plant parts. In a recent study, and in agreement with our results, Salih et al [ 44 ] did not obtain a good polyphenol extraction from macerated or decocted samples when using water as an extractant, in comparison with methanol and ethanol. These results were attributed to the lower polyphenol extraction yield obtained when water was used.…”
Section: Discussionsupporting
confidence: 93%
“…These results were attributed to the lower polyphenol extraction yield obtained when water was used. However, the use of other extracting agents in these conventional techniques entails an optimal extraction of bioactive compounds [ 44 ]. In this sense, methanol’s polarity is higher than ethanol’s; for this reason, very polar phenolic acids, such as cinnamic or benzoic acids, could be extracted more easily, increasing the total polyphenol content in the extracts obtained [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sridevi et al [ 43 ] reported that ElAc from pomegranate peels inhibited M. tuberculosis with an MIC of 0.3–3.5 mg/mL. Salih et al [ 44 ] reported that ElAc from Combretum hartmannianum exerts antimycobacterial activity against Mycobacterium smegmatis (MIC 500–1000 μg/mL) and in another study, the same group [ 45 ] reported that ElAc from Anogeissus leiocarpa exhibited growth inhibitory activity against M. smegmatis with an MIC value of 500 µg/mL. However, to the best of our knowledge, we are the first to report the biological activity of ElAc from B. orellana leaves against Mabs .…”
Section: Discussionmentioning
confidence: 99%
“…In West Africa, Anogeissus leiocarpa leaves are used against zoonotic diseases in traditional medicine [19]. A. leiocarpa exhibits growth inhibitory activity against Mycobacterium smegmatis [20]. Previous studies have focused on investigating the nutritional and microbial properties of A. digitata and A. leiocarpus.…”
Section: Introductionmentioning
confidence: 99%